Peningkatan Mutu Perpustakaan SMK Negeri 7 Pekanbaru Melalui Akreditasi - Hadira Latiar; Rosman H; Nining Sudiar (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2021)
The school library is an institution that acts as a center for information, educational activities, research, recreation for school residents. In supporting this role, school libraries must strive to provide excellent services according to the applicable national library standards. To realize a standardized library, the school library must conduct an assessment through library accreditation. With hope, an accredited library will provide services in accordance with the needs of users. However, awareness of school library accreditation in Riau Province is still very low. This is proven by the number of accredited school libraries that have not reached 1% of the total 1,391 school libraries in Riau Province. This has led to the holding of training and assistance related to school library accreditation for library managers or librarians of SMKN 7 Pekanbaru. The method used in this activity is to conduct training and assistance in preparing accreditation forms and preparing school library accreditation forms. The activity was delivered by means of, interactive discussion, assistance and evaluation using the checklist, pretest and posttest methods.